Problem Konsep Manusia dalam Neo-Darwinisme: Kritik atas Pemikiran Richard Dawkins: The Problem of the Human Concept in Neo-Darwinism: A Critique of Richard Dawkins' Thought - Sutoyo, Yongki; Annada, Fasya Tharra (University of Darussalam Gontor, Indonesia, 2024)
The discourse of human origin is a topic constantly being studied, because human always looking for his meaning and life purpose. One of scientist of Neo-Darwinism, Richard Dawkins, proposed the concept of human with a gene-centric view of evolution. The author uses a descriptive-analysis method to analyze the concept critically. The result is the author found some problems in the concept of human by Richard Dawkins, which human nature reduced to survival machine of replicators genes and memes only. The conclusion of this research is the concept of human by Richard Dawkins affected by naturalism worldview and his ontological commitment to the theory of evolution, made Dawkins define human only from the material side and neglected the immaterial side also other dimensions to comprehend the meaning of human itself